Um Estudo Hermenêutico-Fenomenológico do texto A Origem da Geometria de Edmund Husserl - SOUZA, Ronaldo Araújo de (Universidade Federal do Tocantins, 2023)
This research intends to annex III - whose title is The Origin of Geometry - of the work The Crisis of European Sciences and Transcendental Phenomenology: An Introduction to Phenomenological Philosophy, by Edmund Husserl. Its objective is to explain the pre-scientific in the text The Origin of Geometry, showing how the first geometrists mobilized it for the constitution of geometric idealities; and, in order to accomplish this task, one wonders how the pre-scientific unveiling occurs in the text The Origin of Geometry. In order to constitute the research data, the hermeneutic-phenomenological method is used, seeking to understand the expression in written language with what was shown in the historical encounter between the work and its interpreters. In this movement of understanding, everything that was previously known about the phenomenon is put into epoché, so as not to let the investigating gaze predicate the phenomenon. In the final part of the work, Metacomprehension of the Phenomenon, it explains and articulates with other authors the hermeneutics about the concepts of origin, history, community, language, ideality, among others. As a result of the investigation, it was shown that to unveil the pre-scientific, previous act to the geometric configurations ideas, the imaginative variation articulated to history is mobilized as a movement of spiritual achievements; such realization is understood as “origin”. Also, it takes into account the function of language and intropathy, as well as the fundamental subjectivity/intersubjectivity/objectivity movement for the constitution of ideals. Thus, an a priori of the historical world was presented as a world of things, but not only, whose materials belonging to it served as the basis for the first geometric configurations. The life world is also explained as a foundation of meaning for all sciences that deal with pure space-temporality, taking Geometry in an exemplary sense.